2020
DOI: 10.1371/journal.pone.0230295
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2 receptor ACE2 expression of maternal-fetal interface and fetal organs by single-cell transcriptome study

Abstract: The new type of pneumonia caused by the SARS-CoV-2 (Severe acute respiratory syndrome coronavirus 2) has been declared as a global public health concern by WHO. As of April 3, 2020, more than 1,000,000 human infections have been diagnosed around the world, which exhibited apparent person-to-person transmission characteristics of this virus. The capacity of vertical transmission in SARS-CoV-2 remains controversial recently. Angiotensin-converting enzyme 2 (ACE2) is now confirmed as the receptor of SARS-CoV-2 an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
269
3
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(299 citation statements)
references
References 31 publications
8
269
3
4
Order By: Relevance
“…Using a very permissive threshold of expression of one transcript per cell, only four cells with coexpression were detected in any of the three trimesters, resulting in an estimated < 1/10,000 cells. Our first-trimester data are in agreement with a prior report showing that there is minimal expression of ACE2 at the human maternal-fetal interface [62]; however, the same dataset was recently used to report the opposite [63]. Nonetheless, the co-expression of ACE2 and TMPRSS2 was not examined by either study.…”
Section: Main Textsupporting
confidence: 91%
“…Using a very permissive threshold of expression of one transcript per cell, only four cells with coexpression were detected in any of the three trimesters, resulting in an estimated < 1/10,000 cells. Our first-trimester data are in agreement with a prior report showing that there is minimal expression of ACE2 at the human maternal-fetal interface [62]; however, the same dataset was recently used to report the opposite [63]. Nonetheless, the co-expression of ACE2 and TMPRSS2 was not examined by either study.…”
Section: Main Textsupporting
confidence: 91%
“…To access host cells, SARS-CoV-2 uses a surface glycoprotein (peplomer) known as spike; ACE2 has been shown to be a co-receptor for coronavirus entry [28][29][30]. Therefore, the density of ACE2 in each tissue may correlate with the severity of the disease in that tissue [31][32][33][34][35][36]. Other receptors on the surface of human cells have been suggested to mediate the entry of SARS-CoV-2 [5], including transmembrane serine protease 2 (TMPRSS2) [37,38], sialic acid receptors [39,40], and extracellular matrix metalloproteinase inducer (CD147, also known as basigin) [41].…”
Section: Pathogenesis Of Covid-19mentioning
confidence: 99%
“…SARS-CoV-2 and SARS-CoV are closely related, and both invade human cells via attaching their S proteins to a host transmembrane protein called angiotensin converting enzyme 2 (ACE2) as the entry point 3 . Using transcriptome data, some studies analyzed spatial expression patterns of ACE2 in various tissues and cell types of the human body, and reported that the receptor gene is indeed expressed in the lungs [4][5][6] . The connections between ACE2 expression and viral infection are further supported by cases from the United States, which confirmed for the first time the presence of SARS-CoV-2 in both the upper respiratory tract and stool sample of COVID-19 patients 7 .…”
Section: Introductionmentioning
confidence: 99%